Design and experiments of plasma jet igniter for aeroengine - Yubo Guan; Guorui Zhao; Xinying Xiao (Propulsion and Power Research, 2013)
A plasma jet ignition technology was studied for aeroengine combustor. The advantages of compact structure and advanced performance of air-cooled plasma jet igniter had been tested and verified in the opening test. The plasma jet igniter could produce a continuous plasma jet, stable and reliable ignition. The influence factors of plasma jet ignition aerodynamic and structure were studied in the opening test. Continuous plasma jet was closely related to inlet pressure and flow, simultaneously to the igniter nozzle geometry and throat size. Based on the stable continuous plasma jet, some methods were explored in order to reduce plasma output power, optimize the structure design, and improve the thermal protective. The plasma jet igniter applied to aeroengine combustor was identified initially. For combustion chamber with the igniter, altitude ignition performance were experimented for the inlet pressure of plasma ignition from 10 kPa to 50 kPa, the flow of plasma jet not more than 0.20 g/s, and energy output of ignition from 800 W to 1500 W. The test results were compared with that of conventional aeroengine high energy ignition system. The results show that the plasma jet igniter is better than the conventional one.